Flooding Hazard and Vulnerability. An Interdisciplinary Experimental Approach for the Study of the 2016 West Virginia Floods - Caretta, Martina Angela; Fernandez, Rodrigo; Zegre, Nicolas; Shinn, Jamie (Frontiers in Water, 2021)
The hydrosocial (HS) and social-hydro (SH) frameworks each attempt to understand the complexity of water and society, but they have emerged from historically disparate fields with distinctly different goals as well as methodological and epistemological standpoints. This paper encapsulates the shared experiences of two human geographers and two hydrologists studying hazard and vulnerability in two communities impacted by extreme flooding in West Virginia in 2016. We add to the limited examples of scientists working across epistemologies to improve the understanding of water-societal relations. In so doing, we also contribute to broader discussions of water justice. We outline an experimental approach connecting hydrosocial and social-hydro frameworks to studying flood hazard and vulnerability. Within our conceptualization, we set forth that while social and hydrological factors can be presented as purely anthropogenic or geophysical, respectively, their intersection is the crux to investigate. The relationships between variables of both major categories can help us understand how the social and biophysical systems are interrelated. We depart from 21 semi structured interviews and a secondary analysis of local biophysical factors to develop a model that could show the relations between social and biophysical factors. Linking these factors is crucial step towards integration of SH and HS approaches to create a more comprehensive understanding of water-human relations. These studies can inform policymakers by highlighting where negative connections can be remedied and positive connections can be fostered to emphasize water justice.